Dampak Integrasi Teknologi dalam Pembelajaran Terhadap Prestasi Akademis Mahasiswa Perguruan Tinggi - Rosa Zulfikhar; Mustofa Mustofa; Emmy Hamidah; Heppy Sapulete; Joni Wilson Sitopu; Mike Nurmalia Sari (Journal on Education, 2024)
This study aims to explore the impact of technology integration in learning on the academic achievement of students in higher education. Through a literature review, we investigate the relationship between the use of technology such as e-learning platforms, augmented reality, and virtual reality with student engagement and academic achievement. Findings from this research highlight the importance of adequate technological infrastructure, teacher training, relevant curriculum design, institutional support, and technology accessibility to enhance the effectiveness of technology use in learning. The implications of this study provide insights for education practitioners and policymakers to maximize the benefits of technology in improving student academic achievement in higher education.